Graft thrombosis after coronary artery bypass surgery and current practice for prevention - Harik, Lamia; Perezgrovas-Olaria, Roberto; Soletti, Giovanni; Dimagli, Arnaldo; Alzghari, Talal; An, Kevin R.; Cancelli, Gianmarco; Gaudino, Mario; Sandner, Sigrid (Frontiers in Cardiovascular Medicine, 2023)
Coronary bypass surgery (CABG) is the most commonly performed cardiac surgery worldwide, with over 300,000 procedures performed in the United States annually. The reported incidence of graft failure ranges between 10% and 50%, depending upon the type of conduit used. Thrombosis is the predominant mechanism of early graft failure, occurring in both arterial and vein grafts. We propose a comprehensive review on graft thrombosis and current practice for its prevention. Significant advances have been made in the field of antithrombotic therapy since the introduction of aspirin, which is regarded as the cornerstone of antithrombotic therapy for prevention of graft thrombosis. Convincing evidence now exists that dual antiplatelet therapy (DAPT), consisting of aspirin and a potent oral P2Y12 inhibitor, effectively reduces the incidence of graft failure. However, this is achieved at the expense of an increase in clinically important bleeding, underscoring the importance of balancing thrombotic risk and bleeding risk when considering antithrombotic therapy after CABG. In contrast, anticoagulant therapy has proved ineffective at reducing the occurrence of graft thrombosis, pointing to platelet aggregation as the key driver of graft thrombosis. We will address gaps in knowledge in underrepresented patient populations and discuss potential future concepts for antithrombotic therapy, including P2Y12 inhibitor monotherapy and short-term DAPT.